Transformation framework for legacy software migration - Yusop, N.I; Ku-Mahamud, Ku Ruhana; Othman, Abu Talib (Universiti Utara Malaysia, 2002)
A legacy system is a system that is built using old technologies, but it is still beneficial to an organization. However, today it is facing a great challenge to meet the demands of current applications. Organizations are coming under great pressure to decide on the fate of the legacy system as they try to cope with the changing scenario. Among the alternatives offered are: discarding the legacy system and replacing it with a totally new system, allowing the system to deteriorate until the organization is out of business, redeveloping the system, or reengineering the system. Reengineering seems to offer the best solution to the challenge. This paper focuses on transformation, which is one of the reengneering technologies for migrating a legacy system toward an evolvable system. A few legacy software transformation approaches are discussed. A framework for legacy software migration that combines the strengths of each of the described approaches is proposed.